Metabolic engineering for the production of acetoin and 2,3-butanediol at elevated temperature in Parageobacillus thermoglucosidasius NCIMB 11955 - Sheng, Lili; Madika, Abubakar; Lau, Matthew S. H.; Zhang, Ying; Minton, Nigel P. (Frontiers in Bioengineering and Biotechnology, 2023)
The current climate crisis has emphasised the need to achieve global net-zero by 2050, with countries being urged to set considerable emission reduction targets by 2030. Exploitation of a fermentative process that uses a thermophilic chassis can represent a way to manufacture chemicals and fuels through more environmentally friendly routes with a net reduction in greenhouse gas emissions. In this study, the industrially relevant thermophile Parageobacillus thermoglucosidasius NCIMB 11955 was engineered to produce 3-hydroxybutanone (acetoin) and 2,3-butanediol (2,3-BDO), organic compounds with commercial applications. Using heterologous acetolactate synthase (ALS) and acetolactate decarboxylase (ALD) enzymes, a functional 2,3-BDO biosynthetic pathway was constructed. The formation of by-products was minimized by the deletion of competing pathways surrounding the pyruvate node. Redox imbalance was addressed through autonomous overexpression of the butanediol dehydrogenase and by investigating appropriate aeration levels. Through this, we were able to produce 2,3-BDO as the predominant fermentation metabolite, with up to 6.6 g / L 2,3-BDO (0.33 g / g glucose) representing 66% of the theoretical maximum at 50 ⁰C. In addition, the identification and subsequent deletion of a previously unreported thermophilic acetoin degradation gene (acoB1) resulted in enhanced acetoin production under aerobic conditions, producing 7.6 g / L (0.38 g / g glucose) representing 78% of the theoretical maximum. Furthermore, through the generation of a ΔacoB1 mutant and by testing the effect of glucose concentration on 2,3-BDO production, we were able to produce 15.6 g / L of 2,3-BDO in media supplemented with 5% glucose, the highest titre of 2,3-BDO produced in Parageobacillus and Geobacillus species to date.